Carotenoids and non-alcoholic fatty liver disease - Yilmaz, Bahiddin; Şahin, Kazım; Bilen, Hande; Bahcecioglu, Ibrahim H.; Bilir, Birdal; Ashraf, Sara; Küçük, Ömer (Ame Publishing Company, 2015)
Non-alcoholic fatty liver disease (NAFLD) is a growing health problem around the world, especially in developed countries. NAFLD includes all cases of fatty liver disease from simple steatosis to cirrhosis, without excessive alcohol intake, use of steatogenic medication or hereditary disorders. Pathogenesis is associated with dietary high fat intake, decreased free fatty acid (FFA) oxidation, increased hepatic lipogenesis and lipolysis from the adipose tissue. These metabolic alterations contribute to the hepatic fat accumulation. Consequently, stimulated oxidative stress and inflammation play a major role in hepatocellular damage. Therefore, antioxidant and anti-inflammatory agents may have a role in the prevention of this disease. Carotenoids are potent antioxidant and anti-inflammatory micronutrients, which have been investigated in the prevention and treatment of NAFLD. The main sources of the carotenoids are fruits and vegetables. In this article we review the potential role and possible molecular mechanism of carotenoids in NAFLD.
Keywords: Fatty liver; steatosis; non-alcoholic steatohepatitis; carotenoid; oxidative stress; antioxidant